Communication Improvement Strategies Through Methods Online Learning “Asyncronous and Synchronous” - Sri Musyrifah (Palakka : Media and Islamic Communication, 2021)
This study discusses the Strategy of Improving Communication Through Online Learning Methods “Asynchronous and Synchronous". The purpose of this research is to describe the communication methods used in improving the quality of online learning and to explain the advantages and challenges of using online communication methods to the effectiveness of the learning process. This research is library research or library research. This research explores asynchronous learning methods and synchronous methods. Library research or library research is a series of activities related to methods of collecting library data, reading, and recording and managing library collection materials.  The results of the study indicate that the Asynchronous learning method is a learning communication method where students can interact with each other with the material provided at the time they specify, while the synchronous method refers to a learning or teaching process that occurs simultaneously through an electronic mode. Keywords:  Communication; Online learning; Asyncronous and synchronous.